2016
DOI: 10.1111/neup.12281
|View full text |Cite
|
Sign up to set email alerts
|

WNT‐activated medulloblastoma with melanotic and myogenic differentiation: Report of a rare case

Abstract: Medulloblastoma (MB) with melanotic and myogenic differentiation, previously known as melanotic medullomyoblastoma, is an extremely rare histological variant of MB showing melanocytic as well as skeletal muscle differentiation. Only 10 cases of this rare tumor have been reported in the literature to date. We report this case of a 2-year-old male child who presented with a midline cerebellar mass, which on histopathological examination showed classic MB intermixed with cells containing melanin pigment, along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Interestingly, a neural crest origin has been proposed based on the ultrastructure and proteomic features of its pigment resembling oculocutaneous melanin, including premelanosomes (rather than neuromelanin) [38]. Recently, Rajeshwari et al reported a WNT-activated medulloblastoma with melanotic differentiation and speculated about the potential contribution of neural crest cell progenitors into their pathobiology [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a neural crest origin has been proposed based on the ultrastructure and proteomic features of its pigment resembling oculocutaneous melanin, including premelanosomes (rather than neuromelanin) [38]. Recently, Rajeshwari et al reported a WNT-activated medulloblastoma with melanotic differentiation and speculated about the potential contribution of neural crest cell progenitors into their pathobiology [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ability to perform molecular studies will need to be addressed, as these are providing increasingly powerful evidence for a paradigm shift in the way MBs are approached. 37 http://www.sajo.org.za Open Access support or expertise, historical feedback, data review and paper assessment. J.P. was the primary supervisor and paediatric radiation oncology support/guidance.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Little is known about the molecular classification of these rare medulloblastoma variants and only a few reports have elaborated on their molecular subtyping. [6][7][8] The largest extant series of medullomyoblastomas by Gupta et al concluded that these tumors are not easily classified by the genetic subtypes of medulloblastoma, at least using immunostain surrogates of molecular characteristics. Molecular tests to establish whether these tumors belonged to group 3 or group 4 were apparently not done, and one can infer that these tumors were likely not SHH-activated or Wnt-activated.…”
Section: Discussionmentioning
confidence: 99%
“…Medulloblastoma with myogenic differentiation and melanotic differentiation are considered to be morphological patterns which could be associated with any of the four histological categories 1 . Rarely, tumors can have both myogenic and with melanotic differentiation, as evidenced by a few case reports in literature 4‐6 . Little is known about the molecular classification of these rare medulloblastoma variants and only a few reports have elaborated on their molecular subtyping 6‐8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation